The Zion Christian Church and Global Christianity: negotiating a tightrope between localisation and globalisation - Müller, Retief (Religion, 2015)
South Africa's Zion Christian Church (ZCC) is a primary example of African Indigenous Christianity. This article discusses some of the ways in which a church such as the ZCC might be simultaneously understood as a localised indigenous group, a ‘constructed indigeneity’, as well as inherently belonging to a wider historical tradition of Global Christianity. The discussion proceeds alongside a critical engagement of the sociologist Robert Wuthnow's deconstruction of the ‘Global Christianity Paradigm’, as well as an appropriation of the phenomenologist of religion, James Cox's depiction of ‘indigenous religions’ as an empirically viable theoretical concept, which is demonstrated here as also useful for the purpose of elucidating the type of religiosity encountered in the ZCC. The article makes a plea for a wider acknowledgment of the value of normative approaches to the study of African Christianity and refers to the cultural impact of the theological idea of Incarnation to explain why.
Keywords: Africa – Church history; Africa.; African Zionism; Christian Zionism; Indigenous churches; Jesus Christ; Local church councils; Pilgrims and pilgrimages – Christianity; Theology; Theology; African; Wuthnow; Robert; Zion Christian Church; Zionism